Gender differences in discharge dispositions of emergency department visits involving drug misuse and abuse-2004-2011 - Jennifer I. Manuel; Jane Lee (BMC, 2017)
Abstract Background Drug use-related visits to the emergency department (ED) can undermine discharge planning and lead to recurrent use of acute services. Yet, little is known about where patients go post discharge. We explored trends in discharge dispositions of drug-involved ED visits, with a focus on gender differences. Methods We extracted data from the 2004-2011 Drug Abuse Warning Network, a national probability sample of drug-related visits to hospital EDs in the U.S. We computed weighted multinomial logistic regression models to estimate discharge dispositions over time and to examine associations between gender and the relative risk of discharge dispositions, controlling for patient characteristics. Results The final pooled sample included approximately 1.2 million ED visits between 2004 and 2011. Men accounted for more than half (57.6%) of all ED visits involving drug misuse and abuse. Compared with women, men had a greater relative risk of being released to the police/jail, being referred to outpatient detox or other treatment, and leaving against medical advice than being discharged home. The relative risk of being referred to outpatient detox/drug treatment than discharged home increased over time for men versus women. Conclusions Greater understanding of gender-based factors involved in substance-related ED visits and treatment needs may inform discharge planning and preventive interventions.